A Charge Variant of Bevacizumab Offers Enhanced FcRn-Dependent Pharmacokinetic Half-Life and Efficacy - Singh S.K.; Kumar D.; Nagpal S.; Dubey S.K.; Rathore A.S. (My University, 2025)
Background: Lysine variants of monoclonal antibodies (mAbs) result from incomplete clipping of the C-terminal lysine residues of the heavy chain. Although the structure of the lysine variants has been determined for several mAb products, a detailed study that investigates the impact of lysine charge variants on PK/PD and preclinical safety is yet to be published. Objective: An in-depth investigation of the impact of C- terminal lysine clipping of mAbs on safety and efficacy for bevacizumab charge variants. Method: Charge variant isolation using semi-preparative chromatography is followed by a comparative analysis of FcRn binding, pharmacokinetics, and pharmacodynamics in relevant animal models. Results: K1 variant exhibited improved FcRn binding affinity (4-fold), half-life (1.3-fold), and anti-tumor activity (1.3-fold) as compared to the K0 (main) product. However, the K2 variant, even though exhibited higher FcRn affinity (2-fold), displayed lower half-life (1.6-fold) and anti-tumor activity at medium and low doses. Differential proteomic analysis revealed that seven pathways (such as glycolysis, gluconeogenesis, carbon metabolism, synthesis of amino acids) were significantly enriched. Higher efficacy of the K1 variant is likely due to higher bioavailability of the drug, leading to complete downregulation of the pathways that facilitate catering of the energy requirements of the proliferating tumor cells. On the contrary, the K2 variant exhibits a shorter half-life, resulting only in partial reduction in the metabolic/energy requirements of the growing tumor cells. Conclusion: Overall, we conclude that the mAb half-life, dosage, and efficacy of a biotherapeutic product are significantly impacted by the charge variant profile of a biotherapeutic product. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.